Factors Affecting the Selection of an E-Commerce Website in Bangladesh: E-tailers’ Perspective - Sahel, Samira; Anwar, Tasmia; Nandi, Barnali (International Review of Management and Marketing, 2018)
With the phenomenal growth and rapid pervasion of E-commerce observed in recent time, it becomes crucial on the part of the online retailers in Bangladesh to develop an evaluation criteria system in order to keep up with the fierce competition as well as ensure efficient resource allocation. Prompted by this, the research attempted to investigate the factors that influence the customers in choosing websites for making online purchase. Accordingly, 11 e-tailers from the consumer goods sector have been surveyed and the factors that have been ascertained are- ease of usage, privacy & security, past experience, brand Image, product variety & customer service. Through the employment of Analytical Hierarchical Process the key factors have been ranked. The research reveals that among the chosen factors, ease of usage ranks first securing 45% weight which is followed by privacy & security, past experience, customer service, product variety and brand image. In reaching this judgment, the inconsistency level generated by the synthesis of AHP was 7% which falls below the threshold value of 10%, suggestive of the viability of the result. The implications and findings have been put forward for the e-tailers to make timely decision regarding the features and operations of e-commerce websites. Keywords: E-tail, Analytic Hierarchy Process, Bangladesh. JEL Classifications: M0, M3 DOI: https://doi.org/10.32479/irmm.6447